"Feeding Your Family for a Year, " A Simplified Model for Teaching Students How the Leisure Class Developed. Issue 1 (2nd January 2018) - Wooten, Marian H.
ABSTRACT: This learning activity, "Feeding Your Family for a Year, " teaches students about how the shift from nomadic, hunter-gatherer societies to agrarian societies led to inequities in resources, which in turn allowed a leisure class to develop (Cordes & Ibrahim, 2003). The activity demonstrates how an unequal distribution of resources, represented by candy within the activity, created labor and class distinctions. This understanding helps provide historical background for students who have little knowledge of history and/or are wrestling with complex ideas, such as those presented by Thorstein Veblen in The Theory of the Leisure Class . Recommendations for future use include a variety of modifications: using an item other than candy to signify resources, adding or subtracting an additional indicator of resources, performing the activity outside of a classroom setting, and changing the level of instructor guidance within the activity. At the conclusion of the activity, students should be able to understand how resource inequity led to societal stratification and encouraged people to develop certain skills, resulting in the leisure class, working class, and performer/entertainer class (Cordes & Ibrahim, 2003).